Agglomeration behavior in fluidized-bed evaporator for thermal seawater desalination. (5th October 2015) - Mizuno, Hiroyuki; Kansha, Yasuki; Ishizuka, Masanori; Tsutsumi, Atsushi
Abstract: A novel seawater desalination process using a fluidized-bed evaporator was proposed to prevent scale deposition on the heat-transfer surface for the co-production of salt and pure water. In this evaporator, seawater is fed from the top of the bed and evaporation is caused by collision with heated fluidized particles. Because the liquid feed in the proposed evaporator may cause agglomeration of fluidized particles leading to defluidization, the agglomeration behavior was investigated. Seawater evaporation experiments indicated that when seawater is fed into the fluidized bed, agglomerates of fluidized particles are formed by liquid bridge of seawater feed initially. Subsequently, when liquid bridge breaks during evaporation, solid bridge forms between the particles, leading to their growth. With the repetition of this process, the agglomerates gradually increase. When the size of the grown agglomerates exceeds the mass that can be supported in the bed by the fluidizing gas, the accumulation of agglomerates begins. To describe the agglomeration behavior, we used the force balance of liquid bridge, solid bridge and hydrodynamic forces. Finally, a conceptual model, which can explain the agglomeration behavior, was developed. Highlights: Experiments showed that the proposed process prevents scale formation. The influence of seawater feed on fluidized bed evaporator was investigated. A conceptual model which explains the agglomeration behavior was developed.